Burden of pediatrics hospitalizations associated with Rotavirus gastroenteritis in Lombardy (Northern Italy) before immunization program - Laura Pellegrinelli; Laura Bubba; Valeria Primache; Iacopo Chiaramonte; Franco Maria Ruggeri; Lucia Fiore; Sandro Binda (Istituto Superiore di Sanità, 2015)
AIM: Rotavirus is recognized as the main cause of acute gastroenteritis in children under 5 years old, representing a considerable public health problem with a great impact on social and public health costs in developed countries. This study aims to assess the frequency and the epidemiological aspect of the hospitalization associated with Rotavirus-gastroenteritis in Lombardy, Northern Italy, from 2005 to 2011. METHODS: The Lombardy Hospital Discharge Database was inquired from the official data of the Italian Ministry of Health and investigated for acute gastroenteritis (ICD9CM code for bacteria, parasitic, viral and undetermined etiologic diarrhea) in primary and secondary diagnosis in children < 5 years, between 2005 and 2011. RESULTS: Out of the 32 944 acute-gastroenteritis hospitalizations reported in Lombardy, the 50.8% was caused by Rotavirus infection; of these, the 65.5% were reported in primary diagnosis. The peak of Rotavirus-gastroenteritis hospitalization was observed in February-March in children < 2 years old, with a cumulative prevalence of 64.5%. Patients admitted to hospital with diarrhea of undetermined etiology (about 14% of overall acute-gastroenteritis) showed epidemiological characteristics similar to the Rotavirus-gastroenteritis, suggesting that the virus infection could also be involved in at least some of these. CONCLUSION: Our data confirm that Rotavirus are the most important agents involving in acute gastroenteritis hospitalizations. The use of Hospital Discharge Database had proved to be a simple tool to estimate the burden and to describe the epidemiological characteristics of Rotavirus gastroenteritis and could be used as a surveillance activity before and after the introduction of mass vaccination at national and regional level in Italy.